Identifying the Role of Knowledge Sharing Among Higher Educational Students: Analysis on Degree of Dedication of Undergraduate Students at Limkokwing University, Malaysia - Siew Poh Phung, Dr.; Valliappan Raju, Assoc. Prof. Dr.; Sara Ravan Ramzani, Dr. (International Journal of Engineering and Technology, 2019)
The motive of this research is to comprehend the studentâ€™s impression of information sharing among college undergradutes in Malaysia; the contextual investigation was directed at Limkokwing University of Creative Technology (LUCT), Malaysia.Methodology: A poll was utilized for gathering information from 260 undergraduates from LUCT in Malaysia for the investigation.Findings: Most of the undergradutes suspected that Knowledge Sharing through sharing address notes, control point slides, and other learning assets, among undergradutes will profit everyone, however the present culture does not give adequate help on sharing information. In reality the deliberate idea of sharing data was firmly denied and inspirational state of mind that sharing learning diminishes understudy intensity among companions. Additionally, the greater part of them affirmed that there is absence of cooperation between the individuals who require information and the individuals who can give learning.Conclusion: Our exploration has recognized a few components of learning foundation which are viewed as supporting learning sharing conduct: University culture, University structure, undergradutes, and data assets. This exploration depends on factual investigation to clarify how learning framework can shape information sharing conduct.Â Â